Semimechanistic Physiologically‐Based Pharmacokinetic/Pharmacodynamic Model Informing Epcoritamab Dose Selection for Patients With B‐Cell Lymphomas. Issue 5 (27th September 2022) - Li, Tommy; Hiemstra, Ida H.; Chiu, Christopher; Oliveri, Roberto S.; Elliott, Brian; DeMarco, Dena; Salcedo, Theodora; Egerod, Frederikke Lihme; Sasser, Kate; Ahmadi, Tahamtan; Gupta, Manish
Abstract : Epcoritamab is a CD3xCD20 bispecific antibody (bsAb) that induces T‐cell–mediated cytotoxicity against CD20‐positive B cells. Target engagement and crosslinking of CD3 and CD20 (trimer formation) leads to activation and expansion of T cells and killing of malignant B cells. The primary objective of the dose‐escalation part of the phase I/II trial of epcoritamab was to determine the maximum tolerated dose, recommended phase II dose (RP2D), or both. For bsAbs, high target saturation can negatively affect trimer formation. The unique properties and mechanisms of action of bsAbs require novel pharmacokinetic (PK) modeling methods to predict clinical activity and inform RP2D selection. Traditional PK/pharmacodynamic (PD) modeling approaches are inappropriate because they may not adequately predict exposure–response relationships. We developed a semimechanistic, physiologically‐based PK/PD model to quantitatively describe biodistribution, trimer formation, and tumor response using preclinical, clinical PK, biomarker, tumor, and response data from the dose‐escalation part of the phase I/II trial. Clinical trial simulations were performed to predict trimer formation and tumor response in patients with diffuse large B‐cell lymphoma (DLBCL) or follicular lymphoma (FL). Model‐predicted trimer formation plateaued at doses of 48 to 96 mg. Simulation results suggest that the 48‐mg dose may achieve optimal response rates in DLBCL and FL. Exposure–safety analyses showed a flat relationship between epcoritamab exposure and risk of cytokine release syndrome in the dose range evaluated. This novel PK/PD modeling approach guided selection of 48 mg as the RP2D and provides a framework that may be applied to other CD3 bsAbs.